2023
DOI: 10.1186/s40814-023-01277-3
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of implementing a surgical patient safety checklist: prospective cross-sectional evaluation

Abstract: Background The World Health Organization’s Global Patient Safety Action Plan 2021–2030 call for attention to patient and family involvement to reduce preventable patient harm. Existing evidence indicates that patients’ involvement in their own safety has positive effects on reducing hospitalisation time and readmissions. One intervention reported in the literature is the use of checklists designed for patients’ completion. Studies on such checklists are small scale, but they are linked to reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…During the weeks prior to surgery, patients may experience weight loss and changes in their food intake that will impact upon the validity of the correlation statistics. Previously published analysis showed no difference between genders on responding, but demonstrated that the central community hospital had a higher number of non-responders, possibly indicating that patients with more complex surgery and medical conditions were the ones who participated in the study [ 14 ]. In addition, the modifications to NRS 2002 to customize the screening tool for patients’ self-screening may have affected its reliability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…During the weeks prior to surgery, patients may experience weight loss and changes in their food intake that will impact upon the validity of the correlation statistics. Previously published analysis showed no difference between genders on responding, but demonstrated that the central community hospital had a higher number of non-responders, possibly indicating that patients with more complex surgery and medical conditions were the ones who participated in the study [ 14 ]. In addition, the modifications to NRS 2002 to customize the screening tool for patients’ self-screening may have affected its reliability.…”
Section: Discussionmentioning
confidence: 99%
“…This prospective trial is part of the "Feasibility study of the Patient Safety Checklist (PASC)” to be used by surgical patients before and after surgery, prior to a stepped wedge cluster randomized controlled trial (SW-CRCT) [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations